N-Heterocyclic Carbene Mediated Homoenolate Annulation of Benzofuran-2,3-diones: Stereoselective Synthesis of Bis-Spirofuranones - Seetha Lakshmi, K. C.; Paul, Rony Rajan; Suresh, Eringathodi; Nair, Vijay (Synlett, 2014)
Stereoselective synthesis of bis-spirofuranones via N-heterocyclic carbene catalyzed homoenolate annulations of benzofuran-2,3-diones is reported.
Keywords: NHC; organocatalysis; homoenolate; annulations; spirofuranones